Optimization of Broiler Feed Conversion Ratio by Addition of Probiotics EM-4 and Herbal - Hariyatmi, H; Andayani, Dela Tri Wahyu (Universitas Muhammadiyah Surakarta, 2024)
Effective and efficient broiler management is necessary. The smaller the feed conversion ratio value, the more effective and efficient chicken maintenance. Efforts to reduce feed conversion include reducing feed consumption by adding EM-4 probiotics and herbal spices. The purpose of this study was to determine the effect of the addition of EM-4 probiotics and herbal spices on the feed conversion ratio of broiler chickens (Gallus doemesticus). Experiments were conducted using a sample of 20 broiler chickens aged 14 days, with treatments P0H0 (control), P0H1 (6g herbs), P1H0 (0.6% probiotic EM-4), P1H1 (6% Probiotic EM-4 + 6g Herbs) which were divided into four treatment groups with 5 replicates. The results showed that the treatment with 0.6% EM-4 probiotics + 6 g herbal spices had the lowest feed conversion. Then the effect of probiotics and herbal spices on broiler feed conversion rate was analyzed by Anova test, followed by Duncan test. It can be concluded that the addition of 0.6% EM-4 probiotics and 0.6% herbs is the most optimal feed ratio. These findings can help farmers, entrepreneurs or the general public who use EM-4 and herbs that can optimize their income by reducing the feed conversion ratio of broiler chickens.